Chloroplast ubiquitin E3 ligase SP1: Does it really function in peroxisomes? - Jarvis, RP; Ling, Q; Li, N (American Society of Plant Biologists, 2017)
Pan et al. (2016) presented evidence that the plant ubiquitin E3 ligase SP1 directs proteasome-mediated regulation of the peroxisomal protein import machinery. This was surprising, as SP1 was originally identified as a chloroplast outer envelope-localized regulator of the chloroplast protein import machinery (Ling et al., 2012; Ling and Jarvis, 2015), and there was nothing in the original datasets to suggest functions elsewhere in the cell. It was also difficult to understand how a key regulator of chloroplast protein import, which mediates nuanced and selective effects during development and under stress (Ling et al., 2012; Ling and Jarvis, 2015), could additionally operate in a second organelle with a very different protein import system (Léon et al., 2006). We sought to address these issues by conducting additional experimental analyses.